Determinants of the Intention to Use Performance-Enhancing Substances Among Portuguese Gym Users - Tavares, Ana Sofia R.; Rosado, António Fernando; Marôco, João; Calmeiro, Luis; Serpa, Sidonio (Frontiers in Psychology, 2020)
The present study examined the determinants of the intentions to use prohibited performance- enhancing substances (PES) and the hypothesis of gender and PES use influencing Theory of Planned Behavior (TPB) variables. A TPB approach was used. A convenience sample of Portuguese gym users (n = 453) completed an anonymous web-based survey. Variance-based structural equation modeling, multigroup analysis strategy, latent mean analysis approach and one-way ANOVA analysis were used. The findings showed that, at structural level, results support the TPB framework in terms of characterizing and predicting intentions to PES use in the gym users sample, and that subjective norms were the strongest predictor of PES use intentions. Female and male differed in intentions to use PES, subjective norms and beliefs. However, the predictive model in study remains invariable in both groups. Concerning PES use, results showed the existence of a significant difference, regarding all the TPB´s constructs of the PES users and nonusers’ groups, and that the predictive capacity of each predictor was different for each group. Psychological strategies should be based on subjective norms, alongside beliefs and attitudes towards PES use, since these variables influence the intention to use PES in that particular population.